Between impunity and imperialism : the regulation of transnational bribery - Davis, Kevin E. (New York, NY : Oxford University Press, 2019)
'Between Impunity and Imperialism' describes the legal regime that regulates transnational bribery, identifies and explains the rationales that have guided its evolution, and suggests directions for reform.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 10, 2019).
Keywords: Bribery -- Law and legislation; International business enterprises -- Law and legislation -- Criminal provisions; Corporations -- Corrupt practices